Teaching & learning visual aids: power point and visibility / Chen Ai Hong, Saiful Azlan Rosli and Cosette Yoon Wey Hoe - Chen, Ai Hong; Rosli, Saiful Azlan; Cosette, Yoon Wey Hoe (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Background: Visual aids play an imperative role in lecture delivery today. Visual aids enhance audience engagement and learning experience. The purpose of this study is to provide a better understanding of the illumination setting for Microsoft Office PowerPoint 2011 and its impact on learner's visibility at six-meter viewing distance during a lecture. Methods: The background illumination for Microsoft Office PowerPoint 2011 pre-set at one-quarter (25%), half (50%), three-quarters (75%), and full (100%) transparency levels in the visibility investigation. Visibility was inferred from the reading speed measurement to complete a text projected at six meters. Results: Visibility was affected significantly by different background illumination settings (p<0.05). The best visibility was found in a three-quarters transparency setting. Conclusions: Academicians should be more cautious about their PowerPoint text-background contrast in lecture preparation and delivery to enhance the learning environment.